Adam Watkins Little League Team "Indians" Playing in Water Basin Field - Watkins, Howard::::::::: (1989)
? singing the national anthem; Council Members Les Kimber, Rod Anaforian and Chris Petersen standing in background Ceremony took place at the Wine Press Room at Selland Arena